AMIGA at the Auger observatory: the telecommunications system - Platino, Manuel (2013)
AMIGA is an extension of the Pierre Auger Observatory that will consist of 85 detector pairs, each one composed of a surface water-Cherenkov detector and a buried muon counter. Each muon counter has an area of 30 square meters and is made of scintillator strips, with doped optical fibers glued to them, which guide the light to 64 pixel photomultiplier tubes. The detector pairs are arranged at 433 m and 750 m array spacings. In this paper we present the telecommunications system designed to connect the muon counters with the central data processing system at the observatory campus in Malargue. The telecommunications system consists of a point-to-multipoint radio link designed to connect the 85 muon counters or subscribers to two coordinators located at the Coihueco fluorescence detector building. The link provides TCP/IP remote access to the scintillator modules through router boards installed on each of the surface detectors of AMIGA. This setup provides a flexible LAN configuration for each muon counter connected to a WAN that links all the data generated by the muon counters and the surface detectors to the Central Data Acquisition System, or CDAS, at the observatory campus. We present the design parameters, the proposed telecommunications solution and the laboratory and field tests proposed to guarantee its functioning for the whole data traffic generated between each surface detector and muon counter in the AMIGA array and the CDAS.